Media and Digitalization System in Kazakhstan - Bildebekova, Ә.Т.; Tazhibayev, Ғ.Қ. (Bulletin of L.N. Gumilyov Eurasian National University. JOURNALISM Series, 2018)
The article presents services on digitalization and mass media in Kazakhstan. It is known that in the history of human civilization there were several information breakthroughs. The beginning of this question was based on the modern idea of the «information society» proposed by Japanese scientists in the seventies of the last century. This idea attracted the attention of many countries with its great opportunity for human civilization, the comprehensive and large-scale development of science and education, the improvement of the sociopolitical structure of the state and its sustainable development. Kazakhstan entered a new era - the era of digital technology. The development of the digital industry will give impetus to all other sectors. Some time has passed since the introduction of information and communication technologies, which are the basis of digitization in the country. At the current stage of economic development based on science, education and information technologies, and not on raw materials, the task is to increase the information resource of the country, and find a solution to this issue. Most importantly, transparency and efficiency are created by digitization based on new technologies. From this it follows that digitalization is the future of Kazakhstan. It is clear that this program imposes enormous responsibility on the media and certain responsibilities. Modern trends in the development of the media are turning to the information society. World journalism has moved to a new qualitative level - the production of digital television programs and press products